An intelligent indoor guidance and navigation system for the visually impaired. - Kahraman, M.; Turhan, C. (Assistive Technology, 2022)
Intelligent guidance in complex environments where various procedures are required for navigation is critical to achieving mobility for the visually impaired. This study presents a newly developed software prototype with a hybrid RFID/BLE infrastructure to provide intelligent navigation and guidance to the visually impaired in complex indoor environments. The system enables the users to input their purpose via a specially designed user interface, and provides intelligent guidance through a chain of destination targets which are determined according to the inherent procedures of the environment. Path optimization is performed by adaptation of the traveling salesman problem, and real-time instantaneous instructions are provided to guide the users through the predetermined destination points. For evaluation purposes, a hospital environment is constructed as an example of a complex environment and the system is tested by visually impaired participants. The results show that the intelligent purpose selection and destination evaluation mechanism modules of the system are found to be effective by all the participants.